Biomarkers of Renal Diseases - García-Estañ, Joaquín; Vargas, Felix (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book provides important and updated information on current research devoted to urinary biomarkers. Urinary biomarkers are characteristics that can be objectively measured and evaluated as indicators of normal biological or pathogenic processes of pharmacological responses to therapeutic intervention.